A Decade of Environmental Public Health Tracking (2002-2012): Progress and Challenges. (March 2015) - Kearney, Gregory D.; Namulanda, Gonza; Qualters, Judith R.; Talbott, Evelyn O.
Abstract : Background: The creation of the Centers for Disease Control and Prevention Environmental Public Health Tracking Program spawned an invigorating and challenging approach toward implementing the nation's first population-based, environmental disease tracking surveillance system. More than 10 years have passed since its creation and an abundance of peer-reviewed articles have been published spanning a broad variety of public health topics related primarily to the goal of reducing diseases of environmental origin. Objective: To evaluate peer-reviewed literature related to Environmental Public Health Tracking during 2002-2012, recognize major milestones and challenges, and offer recommendations. Design: A narrative overview was conducted using titles and abstracts of peer-reviewed articles, key word searches, and science-based search engine databases. Main Outcomes: Eighty published articles related to "health tracking" were identified and categorized according to 4 crossed-central themes. The Science and Research theme accounted for the majority of published articles, followed by Policy and Practice, Collaborations Among Health and Environmental Programs, and Network Development. Conclusions: Overall, progress was reported in the areas of data linkage, data sharing, surveillance methods, and network development. Ongoing challenges included formulating better ways to establish the connections between health and the environment, such as using biomonitoring, public water systems, and private well water data. Recommendations for future efforts include use of data to inform policy and practice and use of electronic health records data for environmental health surveillance. Abstract : This article evaluates peer-reviewed literature related to Environmental Public Health Tracking during 2002-2012, recognizes major milestones and challenges, and offers recommendations.